Pertumbuhan Tanaman Lada (Piper nigrum L.) Umur 1 Tahun pada Lahan Bekas Tambang Timah dengan Pemberian Dosis Pupuk Anorganik Tunggal yang Berbeda: Pertumbuhan Tanaman Lada (Piper nigrum L.) Umur 1 Tahun pada Lahan Bekas Tambang Timah dengan Pemberian Dosis Pupuk Anorganik Tunggal yang Berbeda - Eeza Fatwa; Ismed Inonu; Euis Asriani (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2019)
Many research had been done about pepper cultivation in post tin mining area, but there are still have problems with the growth of pepper plants. This is caused by the rapidly decreasing of nutrients available in the post-tin mining area. This research conducted to know the growth response of one-year-old pepper in post-tin mining area by different single inorganic fertilizer doses. And obtaining single inorganic fertilizer dose which gives the best response to the growth of one-year-old pepper in the post-tin mining area. This research began from January to May 2018 in post tin mining area owned by PT. Timah in Dwi Makmur Village, Merawang, Bangka. This study used a Completely Randomized Design (RBD) with a single factor. The factors used were dosages of Single inorganic fertilizer consist DS0(Urea 105 g, TSP 90 g, KCL 80 g), DS1(Urea 125 g, TSP 110 g, KCL 100 g), DS2(Urea 145 g, TSP 130 g, KCL 120 g), DS3(Urea 165 g, TSP 150 g, KCL 140 g), and DS4(Urea 185 g, TSP 170 g, KCL 160 gr). The single dose of inorganic fertilizer showed no significant effect on each growth of variable in pepper, it is possible that the given dose was not effective to stimulate plant growth.